Cyber Cheating sebagai Bentuk Pelanggaran Hak Pasangan Suami Istri dalam Hukum Keluarga Islam: Cyber Cheating as a Form of Violation of Wife's Rights in Islamic Family Law - Hermes Aura Azkiyah; Samsudin, Samsudin; Adang Djumhur (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
The development of digital technology has had a major impact on the dynamics of Muslim households. One phenomenon that has emerged is cyber cheating, which is a form of infidelity committed through digital media. This study aims to analyze cyber cheating as a form of violation of a wife's rights from the perspective of Islamic family law. The approach used is a legal-normative one, examining classical and contemporary Islamic legal sources such as the Quran, hadith, and the opinions of jurists regarding a husband's obligation to maintain his wife's loyalty and honor. The research findings indicate that cyber cheating, despite not involving physical contact, can still be classified as nushuz or a moral violation that impacts fairness in marriage. In QS. An-Nisa verse 128, the importance of maintaining family harmony and preventing nushuz is emphasized, while KHI Article 116 provides the legal basis for divorce due to prolonged disputes. An analysis of the maqashid syariah also shows that cyber cheating has the potential to violate the objectives of sharia, particularly hifzh al-nasl and hifzh al-‘irdh. Thus, cyber cheating is not merely a moral issue but also a serious legal violation of a wife’s rights in Islam. This study is expected to contribute to contemporary Islamic legal literature and serve as a reference for family protection policies for Muslims in the digital age.